Nephrotic Syndrome and AA Amyloidosis Revealing Adult-Onset Cryopyrin-Associated Periodic Syndrome. (June 2013) - Enríquez, R.; Sirvent, A.E.; Padilla, S.; Noguera-Pons, R.; Andrada, E.; Ardoy, F.; Millán, I.; Amorós, F.
<x xml:space="preserve">Abstract</x> Cryopyrin-associated periodic syndrome (CAPS) is due to gain-of-function mutations in the cryopyrin gene, which determines an overactive inflammatory response. AA amyloidosis is a complication of this syndrome. A 53-year-old man was referred to us because of lower limb edema. Past history: at the age of 20, he complained of arthralgia/arthritis and bilateral hypoacusis. At the age of 35, he presented posterior uveitis, several episodes of conjunctivitis, and progressive loss of visual acuity. Laboratory tests disclosed nephrotic syndrome, and renal biopsy showed AA amyloidosis. He was given anakinra with improvement of arthritis. A genetic study revealed the p.D303N mutation in the cryopyrin gene, and he was diagnosed as having AA amyloidosis due to CAPS. Twenty-one months after starting anakinra, the arthritis has disappeared, although nephrotic-range proteinuria persisted. It is important to be aware of cryopyrin-associated periodic syndrome because it can cause irreversible complications, and there is effective therapy.